Extending its tentacles. (Economist, 2001)
Focuses on Microsoft Corp. and its products, including the October 25, 2001 release of its computer operating system, Windows XP. Discussion of Microsoft's marketing strategy and its financial status; Details of products, the Xbox video-game console; Discussion of the .NET software platform for web services; Efforts of rivals to block the release of Windows XP and to limit Microsoft's growth; Outlook for Microsoft.